ANALISIS MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN GEOGRAFI SELAMA BELAJAR ONLINE DI MASA PENDEMI COVID-19 (studi Kasus di SMA Panca Setya Sintang) - Fransiska Praska Nita; Aminuyati Aminuyati; Agus Sugiarto (Universitas Tanjungpura, 2021)
Abstrak This study aims to determine the intrinsic motivation and extrinsic motivation of student learning in geography learning class X IIS 2 SMA Panca Setya Sintang during the Covid-19 pandemic. The research method used is descriptive with qualitative research type case studies. The data sources of this research were students of class X IIS 2 and the data were the results of interviews with geography teachers and X IIS 2 graders in Panca Setya Sintang High School. Data collection techniques through interviews. The results showed that the intrinsic motivation and extrinsic motivation of Panca Setya Sintang high school students' learning motivation was the intrinsic motivation of the desire and motivation in learning geography, this was shown by the student's active learning and strong curiosity. While extrinsic learning motivation of students who are motivated when the teacher gives appreciation in learning, the efforts made by the teacher in motivating students are that the teacher always provides motivation every time learning begins, providing interesting and fun learning. Meanwhile, the efforts made by students are that students study harder and focus on learning. Keywords: Covid-19 Pandemic Period, Geography Learning, Learning Motivation